Upper limb rehabilitation following stroke: current evidence and future perspectives. (December 2013) - Adey-Wakeling, Zoe; Crotty, Maria
Stroke is a leading cause of disability worldwide, with its risk increasing with age. Upper limb hemiparesis is common and associated with persistent impairments and associated disabilities. Older stroke populations often suffer multiple comorbidities and restoring independence is complex. Recovery of upper limb function can be crucial for individuals to return to independent living and to participate in community life. This review describes upper limb recovery post-stroke, and some of the new therapeutic approaches available to promote recovery. Technologies (including virtual reality and telehealth) offer the opportunity for more home-based therapies, longer programs and greater access to rehabilitation for older individuals. However, the trials continue to exclude older individuals, so acceptability is poorly understood. Upper limb rehabilitation remains a research frontier, which has been energized by new technologies, but is grounded by the basic need to find ways to allow older individuals to recover independence. This paper aims to review the applicability and generalizability of current research to the older stoke survivor. Future research priorities need to be tailored to consider the older mean age of individuals in stroke rehabilitation.